Post-translational modification-regulated leukocyte adhesion and migration - Loh, Jia Tong (2016)
Leukocytes undergo frequent phenotypic changes and rapidly infiltrate peripheral and lymphoid tissues in order to carry out immune responses. The recruitment of circulating leukocytes into inflamed tissues depends on integrin-mediated tethering and rolling of these cells on the vascular endothelium, followed by transmigration into the tissues. This dynamic process of migration requires the coordination of large numbers of cytosolic and transmembrane proteins whose functional activities are typically regulated by post-translational modifications (PTMs). Our recent studies have shown that the lysine methyltransferase, Ezh2, critically regulates integrin signalling and governs the adhesion dynamics of leukocytes via direct methylation of talin, a key molecule that controls these processes by linking integrins to the actin cytoskeleton. In this review, we will discuss the various modes of leukocyte migration and examine how PTMs of cytoskeletal/adhesion associated proteins play fundamental roles in the dynamic regulation of leukocyte migration. Furthermore, we will discuss molecular details of the adhesion dynamics controlled by Ezh2-mediated talin methylation and the potential implications of this novel regulatory mechanism for leukocyte migration, immune responses, and pathogenic processes, such as allergic contact dermatitis and tumorigenesis.